2021
DOI: 10.1002/adbi.202000271
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Substrate Promotes Neurotrophic Factor Secretion and Survival of Human Schwann‐Like Adipose Mesenchymal Stromal Cells

Abstract: Mesenchymal stromal cells from adipose tissue (AD‐MSCs) exhibit favorable clinical traits for autologous transplantation and can develop ‘Schwann‐like’ phenotypes (sAD‐MSCs) to improve peripheral nerve regeneration, where severe injuries yield insufficient recovery. However, sAD‐MSCs regress without biochemical stimulation and detach from conduits under unfavorable transplant conditions, negating their paracrine effects. Graphene‐derived materials support AD‐MSC attachment, regulating cell adhesion and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…[ 33 , 49 ]. In recent years, various approaches have been developed to promote induction of MSCs into Schwann-like cells, particularly the use of certain small molecules or growth factors [ 48 , 50 ] and engineered substrates or scaffolds such as graphene oxide substrate [ 51 ], 3D-printed polycaprolactone/polypyrrole (PCL/PPy) conductive scaffold [ 52 ], 3D-printed bionic polycaprolactone (PCL) polymer scaffold [ 53 ], and aligned nanofibers [ 54 ]. Consistent with our recent studies [ 37 ], we, herein, have also demonstrated that GMSCs could directly and rapidly convert into Schwann-like cells when they were encapsulated in methacrylated 3D-collagen hydrogel and cultured under the regular MSC culture medium without the additional introduction of special nutritional and growth factor supplements (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 , 49 ]. In recent years, various approaches have been developed to promote induction of MSCs into Schwann-like cells, particularly the use of certain small molecules or growth factors [ 48 , 50 ] and engineered substrates or scaffolds such as graphene oxide substrate [ 51 ], 3D-printed polycaprolactone/polypyrrole (PCL/PPy) conductive scaffold [ 52 ], 3D-printed bionic polycaprolactone (PCL) polymer scaffold [ 53 ], and aligned nanofibers [ 54 ]. Consistent with our recent studies [ 37 ], we, herein, have also demonstrated that GMSCs could directly and rapidly convert into Schwann-like cells when they were encapsulated in methacrylated 3D-collagen hydrogel and cultured under the regular MSC culture medium without the additional introduction of special nutritional and growth factor supplements (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when cultured in 5% oxygen, the levels of GDNF, BDNF, EGF, IL-1β, and IL-6 increased while the levels of VEGF-A, bFGF, and TGF-β1 decreased [24]. The increased release of growth factors (NGF and GDNF) also occurred with the use of graphene oxide scaffolds, supporting AD-MSCs attachment and regulating cell adhesion and function [23].…”
Section: Low Oxygen Pressurementioning
confidence: 93%
“…Culture Scaffolds/3D Culture/Biomechanical Forces Tissue engineering led to the development of scaffolds and 3D cultures, and these are now widely used to culture MSCs. Three studies evaluated the use of different systems to carry out preconditioning, microfluidic devices [10], encapsulation of MSCs in hydrogel scaffolds [24], and graphene oxide-substrate [23]).…”
Section: Low Oxygen Pressurementioning
confidence: 99%
“…GO is also an applicable substrate in the presence of mesenchymal stromal cells from adipose tissue. It has been employed for enhancing peripheral nerve regeneration, demonstrating good biocompatibility and protection from the surrounding context, and furthermore improving nerve growth factor and glial-derived neurotrophic factor protein secretion [ 25 ].…”
Section: Biomedical Applications Of Gomentioning
confidence: 99%